Factors affecting children and adolescents 50 meter performance in freestyle swimming - Gomez-Bruton, A.; Matute-Llorente, A.; Pardos-Mainer, E.; Gonzalez-Aguero, A.; Gomez-Cabello, A.; Casajus, J. A.; Vicente-Rodriguez, G. (The Journal of Sports Medicine and Physical Fitness, 2016)
BACKGROUND: This study investigated which factors influence performance in a short distance swimming test (50-meters) in adolescent swimmers.